2020
DOI: 10.1080/2162402x.2020.1824863
|View full text |Cite
|
Sign up to set email alerts
|

Tivozanib mediated inhibition of c-Kit/SCF signaling on Tregs and MDSCs and reversal of tumor induced immune suppression correlates with survival of HCC patients

Abstract: The immune modulatory effect of tivozanib, a tyrosine kinase inhibitor, and the underlying immune mechanisms impacting survival of HCC patients have not been investigated. Pre-clinical studies have shown that tivozanib reduces Tregs and MDSCs accumulation through inhibition of c-Kit/SCF axis. We rationalized that c-Kit/SCF axis antagonism by tivozanib may reverse tumor-induced immune suppression in HCC patients. The frequency of circulating Tregs, MDSCs, CTLA-4 + Tregs, PD-1 + T cells, c-Kit + pERK-2 + Tregs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…c-KIT mutations are associated with gastrointestinal, dermatological and hematological tumors [17][18][19][20][21] and c-KIT acts as a biomarker in different cancer types 22,23 . c-KIT expression has also been described in the detection and assessment of the prognosis of patients with tumors 24,25 . Recently the role of c-KIT in the development of bleomycin-induced pulmonary fibrosis was described by Ding et al 26 .…”
mentioning
confidence: 99%
“…c-KIT mutations are associated with gastrointestinal, dermatological and hematological tumors [17][18][19][20][21] and c-KIT acts as a biomarker in different cancer types 22,23 . c-KIT expression has also been described in the detection and assessment of the prognosis of patients with tumors 24,25 . Recently the role of c-KIT in the development of bleomycin-induced pulmonary fibrosis was described by Ding et al 26 .…”
mentioning
confidence: 99%
“…These tumor-infiltrating lymphocytes (TILs) were suggested to be related to the response of immune checkpoints such as PD-1 and PD-L1 [ 25 , 52 ], so that the efficacy of PD-1/PD-L1 inhibitors may be differed between high- and low-risk patients. Meanwhile, in patients from the high-risk group there was a significantly higher abundance of Tregs indicating the suppressive immunotherapy in HCC as reported before [ 53 ], while tivozanib [ 54 ] and cystathionine β -synthase [ 55 ] could decrease Tregs infiltration. Therefore, the combined treatment of immune checkpoint inhibitors, such as PD-1/PD-L1 inhibitors, with the antioxidant drugs and tivozanib or cystathionine β -synthase was highly recommended for the advanced HCC patients with high prognosis score.…”
Section: Discussionmentioning
confidence: 51%
“…Moreover, a very recent trial explored the association of tivozanib (1.5 mg daily for 3 weeks followed by 1-week rest) with nivolumab in 25 mRCC patients (52% pretreated) and reported a promising RR of 56% (including 1 complete response) and a PFS of 18.9 months [32]. Further clinical development of the association of tivozanib with checkpoint inhibitors is therefore warranted in view of the improved tolerability of this TKI and of its immune modulatory properties [5].…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacokinetic studies showed a half-life slightly above 100 h, thus allowing for once-daily administration. Preclinical studies have reported that tivozanib may also have immune modulatory activities by reducing regulatory T cells and myeloid-derived suppressor cell accumulation, and their potential correlation with activity of this drug has recently been reported in a small cohort of patients with hepatocellular carcinoma [5].…”
Section: Introductionmentioning
confidence: 99%